PENGARUH KECERDASAN SPIRITUAL, KECERDASAN EMOSIONAL, DAN PENERAPAN BUDAYA TRI HITA KARANA TERHADAP KECENDRUNGAN KECURANGAN AKUNTANSI (FRAUD) PADA ORGANISASI PERANGKAT DAERAH KABUPATEN BULELENG - Putu Neta Ervinia; Ni Putu Ayu Kusumawati; I Putu Fery Karyada (Hita Akuntansi dan Keuangan, 2021)
Fraud can occur anywhere in any organization or agency. This study aims to determine the effect of spiritual intelligence, emotional intelligence, and the application of Tri Hita Karana culture in handling the tendency of fraud in the Regional Apparatus Organization of the Regency of Buleleng. The population and sample in this study were all financial employees in the Regional Apparatus Organization of the Regency of Buleleng, as many as 151 people. The technique of determining the sample using the saturated sample method. Data were tested using validity test, reliability test, multicollinearity test, heteroscedasticity test, multiple regression analysis, hypothesis test and coefficient of determination. The results showed that the variables of spiritual intelligence, emotional intelligence, and the application of Tri Hita Karana culture negative and significant influences the tendency of fraud in the Regional Apparatus Organization of the Regency of Buleleng.